2015
DOI: 10.1007/s11250-015-0973-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of contagious and environmental mastitis-causing bacteria in bulk tank milk and its relationships with milking practices of dairy cattle herds in São Miguel Island (Azores)

Abstract: This study aimed to assess the degree of contamination of bulk tank milk (BTM) by Staphylococcus spp. and coliform bacteria and to identify major milking practices that help perpetuate them in dairy cattle herds in São Miguel Island. In July 2014, BTM was sampled and a survey concerning local milking practices was conducted on 100 herds. Semi quantitative multiplex polymerase chain reaction detected coagulase-negative staphylococci, Escherichia coli, Staphylococcus aureus, and other coliform bacteria (Klebsiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…Unsanitary handling of the cow’s udder during milking is a frequent source of contamination with S. aureus , which is recognized as a microbial contaminant (Kateete et al 2013). GFP guidelines address those problems through the implementation of protocols through which livestock farmers can control environmental bacteria such as E. coli and S. aureus , which primarily tend to colonize the teat skin (Azevedo et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Unsanitary handling of the cow’s udder during milking is a frequent source of contamination with S. aureus , which is recognized as a microbial contaminant (Kateete et al 2013). GFP guidelines address those problems through the implementation of protocols through which livestock farmers can control environmental bacteria such as E. coli and S. aureus , which primarily tend to colonize the teat skin (Azevedo et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, S aureus can be isolated from several utensils used during milking as well as from animal body surfaces and the hands of the milking operator (Benić and others 2012). In a recent study (Azevedo and others 2016), the authors observed, using a six-point scale, that the poor hygiene during milking is an important risk factor for Azorean herds. Unfortunately, the milking machine maintenance and their vacuum levels and even the teat’s condition of dairy cows were not assessed, and further studies were needed in order to evaluate the impact of these factors in the incidence of S aureus .…”
Section: Discussionmentioning
confidence: 99%
“…All procedures concerning the collection and preparation of samples, DNA extraction, and PCR and qPCR amplification for this study were reported by Azevedo and others (2016).…”
Section: Methodsmentioning
confidence: 99%
“…E. coli was found to usually infected mammary gland of cows parturition and early lactation period which could lead to local and acute mastitis (Burvenich et al, 2003). In a study in Portugal, E. coli was found to be the second most common bacteria after non-coagulative staphylococci found in bulk tank milk (Azevedo et al, 2016). In Uruguay, E. coli was second only to S. aureus in bovine subclinical mastitis cases (Gianneechini et al, 2002), whereas in China, it was one of the leading types of coliform bacteria found in milk from cows with subclinical mastitis (Memon et al, 2013; Wang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%